Comparative analysis of nominal and real convergence in West African Monetary Zone (WAMZ): Time varying parameter approach - Olorunsola E. Olowofeso; Ebrima N. Wadda; Joachim Loua; Kayode Ezekiel Adedeji; John M. Collins; Emmanuel Akutcha (West African Monetary Institute (WAMI), 2023)
This study estimates the rate and distance to convergence of WAMZ Member States and provides a comparative analysis of nominal and real convergence to evaluate WAMZ's preparedness for monetary integration. We employ monthly data on the consumer price index and nominal exchange rate from January 2003 to December 2022 to assess nominal convergence, while annual real GDP growth rate data from 1980 to 2022 is used to evaluate real convergence among member states. The findings of the study reveal some evidence of convergence in exchange rates, especially for Guinea and Liberia. For inflation, there is no evidence of convergence; however, some countries are catching up. Regarding real convergence, there is no evidence of convergence towards the criteria, with only Ghana seeming to converge towards the reference country, Nigeria. The results showed little support for convergence, as evidenced by the estimated higher distance to convergence on average by member states. The study highlights that recent external macroeconomic shocks have hindered convergence efforts, necessitating policies to enhance resilience. It emphasizes the importance of prioritizing nominal convergence to achieve long-term economic stability and integration in the region
Keywords: E31; O47; F31; 330; Convergence; Inflation; Exchange rate; Growth; Time-varying parameters